Shareholder Wealth and Wages: Evidence for White‐Collar Workers - Bronars, Stephen G.; Famulari, Melissa (Journal of Political Economy, 2001)
We present empirical evidence on the relationship between individual wages, conditional on worker characteristics, and equity returns using a unique survey from the Bureau of Labor Statistics. Equity returns affect the wages only of workers with three or more years of tenure. A 4 percent increase in a firm's market value raises pay by 0.3 percent within three years. Our estimates suggest that each $10 increase in shareholder wealth raises the present value of a firm's wage bill by $1. The elasticity of white‐collar wages with respect to equity returns is one‐third smaller than the CEO salary elasticities in our sample.